HISTORY OF FORCED RESIDENCE IN EASTERN KAZAKHSTAN IN THE 1930s. - Джакипова, Танакоз (Вестник КазНПУ имени Абая. Серия: Исторические и социально-политические науки, 2021)
This articleis dedicated the first deportation of the Polish people to Kazakhstan after political changes in the country, including the first arrival of Poles in East Kazakhstan. The process of resettlement of Germans and Koreans, as well as Poles began in 1930. Especially majority of immigrants in Kazakhstan were Koreans. Besides, it is written about the history of the German and Polish peoples, who were first deported to Kazakhstan from Ukraine and Russia. The article is based on the growth of German settlements in the Akmola, Semey, Pavlodar, Omsk and Barnaul regions at the beginning of the 20th century. The repressions of 1937-1938 had a special impact on the socio-demographic development of the population of the East Kazakhstan region. The local population has decreased, but the population growth has occurred at the expense of other nationalities.